2012
DOI: 10.1103/physrevlett.108.083002
|View full text |Cite
|
Sign up to set email alerts
|

Exact Wave Functions of Two-Electron Quantum Rings

Abstract: We demonstrate that the Schrödinger equation for two electrons on a ring, which is the usual paradigm to model quantum rings, is solvable in closed form for particular values of the radius. We show that both polynomial and irrational solutions can be found for any value of the angular momentum and that the singlet and triplet manifolds, which are degenerate, have distinct geometric phases. We also study the nodal structure associated with these two-electron states. Quantum rings are usually modelled by electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 40 publications
3
68
0
Order By: Relevance
“…The Pauli hyperplanes are only a subset of the full nodes and it is interesting to note that these nodes are related to the 1D nodes. 24,27,32 The non-interacting nodes are represented in Fig. 1 for a given position of the first electron Ω 1 = (π/6, 0), which is represented by a small yellow sphere.…”
Section: Non-interacting Wave Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pauli hyperplanes are only a subset of the full nodes and it is interesting to note that these nodes are related to the 1D nodes. 24,27,32 The non-interacting nodes are represented in Fig. 1 for a given position of the first electron Ω 1 = (π/6, 0), which is represented by a small yellow sphere.…”
Section: Non-interacting Wave Functionsmentioning
confidence: 99%
“…This result is not surprising because we know that excited states must have additional nodes in order to be orthogonal to the lowest-energy state, and these additional nodes are usually not imposed by symmetry. 24 …”
Section: Proof Of the Exactness Of The Nodesmentioning
confidence: 99%
“…In Ref [39], we built a GLDA correlation functional ε c [ρ(r), η(r)] based on the "electrons-on-a-ring" paradigm (also called ringium) which corresponds to electrons on a ring interacting through the ring [47][48][49] (see Appendix A).…”
Section: B Generalized Local-density Approximationmentioning
confidence: 99%
“…In particular, we have shown that one can solve the Schrödinger equation for two electrons confined to a ring [12] or to the surface of a sphere [10,11] for particular values of the ring or sphere radius. In particular, we showed that some of the solutions exhibit the Berry phase phenomenon, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we showed that some of the solutions exhibit the Berry phase phenomenon, i.e. if one of the electrons moves once around the ring and returns to its starting point, the wave function of the system changes sign [12]. Subsequently, Guo et al reported some exact solutions for two vertically coupled quantum rings using the same technique [13] but their analysis is incomplete [14].…”
Section: Introductionmentioning
confidence: 99%